Black Jacobins in Contemporary France: On Identities on Politics, Decolonial Critique, and the Other Blackness. Issue 1 (2nd January 2016) - Thompson, Vanessa Eileen
Abstract : Formerly, issues of race were written out of the public landscape of the French Republic. Now the "black condition" is openly debated. This shift is informed by self-identified black movements and their responses to French Republican avoidance of thematizing racialized social inequalities. It is simultaneously contested by groups that experience anti-black racism as it reduces their alternate use of race and ethnicity. Does blackness lead to the homogenization of black experiences or can it initiate solidarity? This article examines current debates on blackness in Paris by drawing upon ethnographic activist research with a black activist group. I analyze how the group maneuvers through a supposedly race-blind discourse, in which the act of identifying race risks being disqualified as communitarian. I argue that a conception of blackness is introduced that provides the potential to recognize the pluralities of blackness, re-shaping notions of blackness, and the abstract Republican model itself.